A numerical analysis of two dimensional lid driven cavity flow using cubic interpolated pseudo-particle method - Idris Mat Sahat, 1983-; Nor Azwadi Che Sidik, supervisor; Fakulti Kejuruteraan Mekanikal (2010)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2010